2t+8+1/5t-t=11

Simple and best practice solution for 2t+8+1/5t-t=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2t+8+1/5t-t=11 equation:



2t+8+1/5t-t=11
We move all terms to the left:
2t+8+1/5t-t-(11)=0
Domain of the equation: 5t!=0
t!=0/5
t!=0
t∈R
We add all the numbers together, and all the variables
t+1/5t-3=0
We multiply all the terms by the denominator
t*5t-3*5t+1=0
Wy multiply elements
5t^2-15t+1=0
a = 5; b = -15; c = +1;
Δ = b2-4ac
Δ = -152-4·5·1
Δ = 205
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$t_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$t_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$t_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-15)-\sqrt{205}}{2*5}=\frac{15-\sqrt{205}}{10} $
$t_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-15)+\sqrt{205}}{2*5}=\frac{15+\sqrt{205}}{10} $

See similar equations:

| 8(y-3y=6(2y-6 | | -6.5+x=14.12 | | -4x+8+5x=-13+17 | | 1x-9=-12 | | 3r^2-20r-7=0 | | 1–8z=9 | | 10r–10=10 | | f=4-8 | | |5x-5|/4=5 | | 8/5x+4/3=1/15 | | -7+8n=9 | | 9x2-5=-23 | | 42/y=2 | | 24+0.44=19+1.69x | | x(6x-13)=5 | | 2z-3=-7 | | 12m+9=8m+13 | | 10n-14=7n-16+3n+2 | | 1x(6x-13)=5 | | 9c+10=1 | | 1,04^x=7*1,02^x | | -3a+12=36 | | 2p+2=-2 | | q+8=6 | | 2w-3^=4 | | 3q+9=3 | | -3(x-5)=-18 | | (x-7)^2=1 | | 2w+7=4.6 | | 2(3x+3)=8x+4-2x+2 | | 1.1^x=100 | | 2b+66=9 |

Equations solver categories